Penggunaan Social Media Marketing Instagram @tvmuhammadiyah Dalam Membangun Customer Engagement - Oktaviana Anggraini; Jamiati KN (Lembaga Pengembangan Kinerja Dosen, 2023)
Muhammadiyah Television is a television media that has an Instagram account with the name @tvmuhammadiyah to educate audiences on Instagram. This research aims to find out the extent of the use of social media marketing on tvMu's Instagram, how to build customer engagement on tvMu's Instagram, inhibiting and supporting factors in building customer engagement. The theories used in this research are social media marketing theory from As'ad and Alhadid (2014) and customer engagement theory from Evans et al. (2021), where this research uses a qualitative approach with descriptive methods accompanied by data collection techniques using observation and in-depth interviews as complementary evidence. The results of this research show that tvMu uses social media marketing strategies such as creating interesting content, changing the appearance of the feed, scheduling regular content upload hours, attracting young talent, but has obstacles such as minimal audience interaction on Instagram with limiting factors for tvMu in distributing content.